A checklist of indigenous flora in the Richtersveld National Park confirms high plant diversity in the arid north-western tip of South Africa - Pieter van Wyk; Hugo Bezuidenhout; Norbert Jürgens (Koedoe: African Protected Area Conservation and Science)
As a basis for conservation planning, a first comprehensive vascular plant species checklist for the core Richtersveld National Park was compiled, based on the collection of more than 3000 new herbarium vouchers and in total studying over 8000 specimens and more than 4000 iNaturalist observations. By the end of April 2024, a total of 1077 indigenous taxa were recorded. The documented indigenous flora included 14 pteridophytes, 3 paleodicots, 246 monocotyledons and 815 dicotyledons. A total of 99 indigenous families and 392 genera were recorded. The largest family was the Asteraceae, and the second largest family was the Aizoaceae. In addition, 44 taxa were identified as invasive or alien flora. Seven species were regarded as extinct; of these, four species disappeared in a context of diamond mining, and three species were no longer found after the recent drought 2014 to 2022. The role of the peculiar biogeographical position and the high diversity of unique habitats within extreme environmental gradients were discussed in a review of published evidence. Reference to distribution and habitat was presented for each species in the appendices.